Review of effects of dielectric coatings on electrical exploding wires and Z pinches. (18th September 2017) - Wu, Jian; Li, Xingwen; Li, Mo; Li, Yang; Qiu, Aici
Abstract: As the most powerful x-ray source in the laboratories, the wire array Z pinches have been of great relevance to inertial confinement fusions, laboratory astrophysics, and other high-energy density applications. In order to produce x-ray with greater power and higher efficiency, the dynamics of wire array has been investigated extensively, and various methods have been proposed to improve the implosion quality of the wire array. This review focuses on the experimental and theoretical investigations regarding the effects of the dielectric coatings on electrical exploding wires and Z pinches. Since the early 2000, the electrical wire explosion related to the first stage of the wire array Z pinches has been studied extensively, and the results indicated that the dielectric coatings can significantly increase the joule energy deposition into a wire in the initial stage, and even the corona free explosion of tungsten wires can be achieved. Recently, there is an increasing interest in the dynamics of insulated wire array Z pinches. By applying dielectric coatings, the ablation process is suppressed, the x-ray start time is delayed, and the possibility of multi-peak radiation is decreased. This review is organized by the evolution dynamics of wire array Z pinches, and a broad introduction to relevant scientific concepts and various other applications are presented. According to the current research status, the challenges, opportunities and further developments of Z pinch loads using dielectric coatings are proposed to further promote the researches and their applications.